2015
DOI: 10.1017/s0022377815001348
|View full text |Cite
|
Sign up to set email alerts
|

Imposed magnetic field and hot electron propagation in inertial fusion hohlraums

Abstract: The effects of an imposed, axial magnetic field B z0 on hydrodynamics and energetic electrons in inertial confinement fusion (ICF) indirect-drive hohlraums are studied. We present simulations from the radiation-hydrodynamics code HYDRA of a low-adiabat ignition design for the National Ignition Facility (NIF), with and without B z0 = 70 Tesla. The field's main hydrodynamic effect is to significantly reduce electron thermal conduction perpendicular to the field. This results in hotter and less dense plasma on th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
18
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 26 publications
0
18
0
Order By: Relevance
“…Previous work has considered the effect of an imposed field on capsule performance 4 and hohlraum conditions. 19 Simulations are performed using the radiation-hydrodynamics code HYDRA 20 both with and without MHD 21 included. Here, kinetic and nonlocal effects on heat transport are neglected.…”
Section: Introductionmentioning
confidence: 99%
“…Previous work has considered the effect of an imposed field on capsule performance 4 and hohlraum conditions. 19 Simulations are performed using the radiation-hydrodynamics code HYDRA 20 both with and without MHD 21 included. Here, kinetic and nonlocal effects on heat transport are neglected.…”
Section: Introductionmentioning
confidence: 99%
“…The MagnetoInertial Fusion Electric Discharge System has been developed to provide steady state magnetic fields for long time-scales relative to the experiments. An experiment on the Omega Laser Facility with a 7.5 T external axial magnetic field imposed on an Omega-scale hohlraum measured a rise in observed temperature along the hohlraum axis [5] and modeling showed that external fields can guide hot electrons from laser-plasma interactions [6] through the hohlraum, rather than the capsule [7]. From Ohm's Law, it has been shown that electron heat transport advects such magnetic fields through the Nernst effect [8][9][10][11][12][13][14] in addition to well-known processes like "frozen-in-flow" and resistive diffusion.…”
mentioning
confidence: 99%
“…Accurate modeling of these quantities has implications for laser plasma interactions [5,6] and hot electron propagation [7] in the gas fill and understanding hot spots on the dense plasma that generate X-rays. The kinetic electron transport and B field physics presented here could affect details of X-ray drive if incorporated into full-scale radiationhydrodynamics modeling (including reduced phenomenological laser-plasma interaction models) of indirect drive with externally applied B-field.…”
mentioning
confidence: 99%
“…The prescribed 2-D time-dependent radiation drive asymmetry 14 is incorporated from the beginning of the drivephase. Magnetic field effects on the hohlraum (which can affect the radiation asymmetry 27,28 ) are not considered here. At 15.7 ns, which corresponds to the peak radiation temperature, the 2-D simulations are reconstructed into 3-D Cartesian for the stagnation phase.…”
Section: Simulation Setupmentioning
confidence: 99%